Radionuclides in drug development - Uhl, Philipp; Fricker, Gert; Haberkorn, Uwe; Mier, Walter (Drug discovery today, 2015)
Recently, molecular imaging has gained broad interest for the stratification procedures in personalized therapies. In this regard, the importance of radionuclides for the drug development process shall not be underestimated. The methods range from target identification, pharmacokinetics studies, Phase 0 microdosing studies, endoradiotherapy with low molecular weight drugs to radioimmunotherapeutics such as Zevalin®. This review provides a comprehensive overview of the use of radionuclides in medical sciences from autoradiography over radioimmunoassay, post-labeling and target identification to the determination of the pharmacokinetics and metabolization and molecular imaging techniques. We demonstrate the enormous potential of different radionuclides with respect to specific classes of drugs, the radiolabeling procedures and their limitations, the instrumentation technologies and their implementation in the drug development process.